Radiometric Stability Validation of 17 Years of AIRS Data Using Sea Surface Temperatures. Issue 21 (5th November 2019) - Aumann, Hartmut H.; Broberg, Steve; Manning, Evan; Pagano, Tom
Abstract: We evaluate the stability of the radiometric calibration of the Atmospheric Infrared Sounder (AIRS) by analyzing the trend in the time series of the difference between the brightness temperatures measured in the 1, 231‐cm −1 atmospheric window channel, corrected for atmospheric transmission, relative to the Real‐Time Global Sea Surface Temperature (RTGSST) for oceans between 30S and 30N. The observed bias relative to the RTGSST between 2002 and 2019 was less than 250 mK, with a 2–3‐mK/yr trend. Establishing the stability of the 1, 231‐cm −1 channel at tropical ocean temperatures at the 2–3‐mK/yr level is a necessary but not sufficient condition of establishing the calibration stability of all AIRS channels over the full dynamic range at a comparable level. Our analysis indirectly establishes the stability of the RTGSST for the 2002–2017 time period and region at the 2–3‐mK/yr level, with a degradation since 2017. Key Points: For climate research trend artifacts in the measurements have to be less than 10 mK/yr. At least for one AIRS atmospheric window channel, the trend relative to the RTGSST is about 2‐3 mK/yr. At the 2‐3 mK/yr level the stability of the reference source may become questionable, and contribute to the trend.